Pendidikan Agama Islam Berbasis Kesadaran Diri untuk Mengatasi Krisis Moral Remaja - Dwi Restiana (Mataram University, 2025)
Moral crisis among adolescents has become a serious concern in contemporary society, marked by declining ethical behavior, weakening religious commitment, and increasing social deviance. Islamic Religious Education (PAI) is expected to play a strategic role in addressing this issue. This study aims to analyze the concept of self-awareness-based Islamic Religious Education as an effort to counter adolescent moral crisis. This research employed a qualitative library research approach by reviewing recent journal articles, books, and relevant scientific publications. The results indicate that self-awareness-based PAI emphasizes internal reflection, moral consciousness, and spiritual responsibility, enabling adolescents to internalize Islamic values as personal commitments rather than external obligations. Integrating self-awareness into PAI learning strengthens moral reasoning, emotional regulation, and spiritual intelligence, which are essential in facing moral challenges in the modern era. Therefore, self-awareness-based Islamic education is a relevant and effective approach to preventing adolescent moral crisis.